Long-term administration of aqueous garlic extract (AGE) alleviates liver fibrosis and oxidative damage induced by biliary obstruction in rats - ERCAN, FERİHA; ŞENER, GÖKSEL; KABASAKAL, LEVENT; ŞİRVANCI, SERAP (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The aim of this study was to assess the antioxidant and antifibrotic effects of chronic administration of aqueous garlic extract on liver fibrosis induced by biliary obstruction in rats. Liver fibrosis was induced in male Wistar albino rats by bile duct ligation and scission (BDL). Aqueous garlic extract (AGE, 1 ml/kg, i.p., corresponding to 250 mg/kg) or saline was administered for 28 days. At the end of the experiment, rats were killed by decapitation. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) levels were determined to assess liver functions and tissue damage, respectively. Tumor necrosis factor-alpha (TNF-alpha) was also assayed in serum samples. Liver tissues were taken for determination of the free radicals, renal malondialdehyde (MDA) levels, an end product of lipid peroxidation; glutathione (GSH) levels, a key antioxidant; and myeloperoxidase (MPO) activity, as an indirect index of neutrophil infiltration. Hepatic collagen content, as a fibrosis marker was also determined. Serum AST, ALT, LDH, and TNF-alpha levels were elevated in the BDL group as compared to control group, while this increase was significantly decreased by AGE treatment. Hepatic GSH levels, significantly depressed by BDL, were elevated back to control levels in AGE-treated BDL group. Increases in tissue free radical and MDA levels and MPO activity due to BDL were reduced back to control levels by AGE treatment. Similarly, increased hepatic collagen content in the BDL rats was reduced to the level of the control group with AGE treatment. Since AGE administration alleviated the BDL-induced oxidative injury of the liver and improved the hepatic structure and function, it seems likely that AGE with its antioxidant and antifibrotic properties, may be of potential therapeutic value in protecting the liver fibrosis and oxidative injury due to biliary obstruction. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: garlic; bile duct ligation; fibrosis; oxidative damage; VASCULAR ENDOTHELIAL-CELLS; HEPATIC STELLATE CELLS; BILE-DUCT LIGATION; MYELOPEROXIDASE ACTIVITY; SUPEROXIDE-DISMUTASE; LIPID-PEROXIDATION; S-ALLYLCYSTEINE; RENAL DAMAGE; STRESS; INJURY